Centro de investigación y alerta ambiental Sabana Centro: Borde permeable de servicios periféricos (2017)
After a general analysis of the northern region we identify the shortcomings and benefits that the sector offers to the city and the region itself, where we verify that after the high demand that Bogota presents with respect to administrative, educational and all kinds of needs Services rendered to the region, the edges of the city should be used as a tool to reduce the population's floating income to the city, edges that must be permeable but must have all the equipment that lead to this goal; From means of transportation conducive to demand as elements of environmental protection that diminish the impact that they generate.